Embryo and larval biology of the deep-sea octocoral Dentomuricea aff. meteor from the Azores under two temperature regimes - Rakka, Maria; Godinho, António; Orejas, Covadonga; Carreiro-Silva, Marina (PANGAEA, 2022)
The study focuses on the early life stages of the species Dentomuricea aff. meteor, a common deep-sea octocoral in the Azores. The objective was to describe the embryo and larval development, survival and swimming behaviour of early life stages of the target species, under two temperature regimes, corresponding to the minimum and maximum temperatures in its natural environment during the spawning season (13°C and 15°C). Embryo and larval development were monitored closely and revealed faster developmental rates under 15°C. Survival counts were performed throughout embryo and larval development, but were not statistically different between temperatures. Moreover, swimming behaviour was assessed by means of video recordings, revealing a higher larval swimming speed at 15°C. Additional data on larval behaviour are provided, including settlement and metamorphosis rates which were low for both temperatures. Our results showcase how small temperature fluctuations can affect embryo and larval characteristics, potentially impacting larval dispersal and success.
Keywords: Atlantic; Cold-water coral; Deep-sea; Dispersal; early life stages; Laboratory experiment; larval development; larval swimming